EMPLOYMENT GAP ANALYSIS FOR WOMEN IN THE PUBLIC SECTOR: STUDY ON ALUMNI OF STAIN/IAIN SAMARINDA IN EAST AND NORTH KALIMANTAN - Hidayati, Diajeng Laily; Noor, Widya Noviana (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Despite its low current level, the number of women employed in the public sector continues to increase annually. However, the positive advancement of women's roles in Indonesia's public sector still encounters numerous challenges. Cultural barriers, social norms, religious perspectives, and non-gender-responsive policies are among the factors hindering women's participation in the public sphere. Thus, this study aims to analyze the perceptions of female alumni from IAIN Samarinda regarding the status of women working in the public sphere, examine the factors that encourage and impede female alumni from IAIN Samarinda to pursue careers in public spaces. This study is qualitative research employing a phenomenological approach involving 101 informants who are alumni of STAIN/IAIN Samarinda. Data collection was conducted through questionnaires, interviews, and documentation. Findings were categorized according to themes and key codes that emerged during the data analysis process. The study findings demonstrate that employment opportunities have opened up for female alumni from STAIN/IAIN Samarinda. The majority of alumni secure employment for a period of 6-12 months, and most respondents believe that women have equal opportunities as men to work in public spaces. Factors supporting female alumni from STAIN/IAIN Samarinda in pursuing careers in the public sector include spousal permission for married individuals and familial consent for unmarried individuals. Moreover, economic motives, self-actualization, and social responsibility are additional factors driving women to work in public spaces. Conversely, factors impeding female alumni from STAIN/IAIN Samarinda in working within public spaces encompass religious interpretations, the belief that wives should remain at home, and the perception of domestic duties assigned to women.Meskipun masih rendah, saat ini, jumlah perempuan yang bekerja di sektor publik terus meningkat dari tahun ke tahun. Meski demikian, peningkatan positif peran perempuan di sektor publik di Indonesia masih banyak menuai tantangan. Tantangan budaya, norma sosial, pandangan keagamaan, dan kebijakan yang tidak responsif gender merupakan beberapa hal yang menghambat perempuan bekerja di ruang publik. Penelitian ini, oleh karena itu, bertujuan untuk menganalisis persepsi alumni perempuan IAIN Samarinda tentang status bekerja pada ruang publik di kalangan perempuan; menganalisis faktor apa saja yang mendorong dan menghambat perempuan alumni IAIN Samarinda untuk bekerja di ruang publik. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologis dengan melibatkan 101 informan yang merupakan alumni STAIN/IAIN Samarinda. Pengumpulan data dilakukan melalui angket, wawancara, dan dokumentasi. Temuan dikategorikan menurut tema dan kode penting yang muncul selama proses analisis data. Hasil penelitian menujukkan bahwa kesempatan kerja bagi perempuan alumni STAIN/IAIN Samarinda telah terbuka. Mayoritas alumni mendapatkan pekerjaan 6-12 bulan dan sebagian besar responden berpendapat bahwa perempuan memiliki kesempatan yang sama dengan laki-laki untuk bekerja di ruang publik. Faktor-faktor yang mendukung perempuan alumni STAIN/IAIN Samarinda bekerja di sektor publik adalah ijin yang diberikan oleh suami bagi yang telah menikah dan izin keluarga bagi yang belum menikah. Selain itu, motif ekonomi, aktualisasi diri dan tanggung jawab sosial juga menjadi alasan perempuan bekerja di ruang publik. Di sisi lain, faktor yang menghambat perempuan alumni STAIN/IAIN Samarinda bekerja di ruang publik adalah pemahaman agama, pemahaman bahwa istri harus menetap di rumah, dan pandangan kewajiban domestik yang harus dikerjakan perempuan.